Pengaruh Kualitas Pelayanan Dan Promosi Penjualan Terhadap Volume Penjualan Suretybond PT. Parolamas Cabang Jayapura - Slamet Pamujianto; Ningrum Astriawati; Handoyo Widyanto; Fatrodin Fatrodin; Sumardi Sumardi (Jurnal Riset dan Inovasi Manajemen, 2023)
Surety bond insurance issuance services are an important sector in the construction and service industry, because they involve insurance institutions on the quality and success of projects to clients. This study aims to determine the effect of service quality and sales promotion on Suretybond sales volume at PT. Parolamas Jayapura branch quality of service and sales promotion to the sales volume of suretybond PT. Parolamas Jayapura branch. The sample taken in this study was 100 respondents with random sample. The data analysis technique in this study uses multiple linear regression analysis with simultaneous regression test (F-test) and partial regression test (t-test). The results showed that there was a positive influence of service quality and sales promotion on the sales volume of suretybond PT. Parolamas Jayapura Branch. Quality of service and promotion is able to explain Sales volume by 81.1%, while for 18.9% sales volume is influenced by variables other than service quality and sales Promotion.